2021
DOI: 10.3390/cells10061493
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles and Their miRNA Content in Amniotic and Tracheal Fluids of Fetuses with Severe Congenital Diaphragmatic Hernia Undergoing Fetal Intervention

Abstract: Infants with congenital diaphragmatic hernia (CDH) are at high risk of postnatal mortality due to lung hypoplasia and arterial pulmonary hypertension. In severe cases, prenatal intervention by fetal endoscopic tracheal occlusion (FETO) can improve survival by accelerating lung growth. However, postnatal mortality remains in the range of about 50% despite fetal treatment, and there is currently no clear explanation for this different clinical response to FETO. We evaluated the concentration of extracellular ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…EVs are present in many biological fluids, including amniotic fluid [ 40 , 41 ], because they are released by fetal epithelial cells from skin, urine, and lungs [ 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Recent data suggested that intraamniotic EV could contain biomarkers relating to a wide spectrum of fetal disorders including bacterial intra-amniotic infection [ 30 , 40 , 45 , 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…EVs are present in many biological fluids, including amniotic fluid [ 40 , 41 ], because they are released by fetal epithelial cells from skin, urine, and lungs [ 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Recent data suggested that intraamniotic EV could contain biomarkers relating to a wide spectrum of fetal disorders including bacterial intra-amniotic infection [ 30 , 40 , 45 , 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…hAF-EVs have been described to be relatively small in size (around 100 nm) with the expression of canonical exosomal markers [ 61 ]. hAF-EVs have been exploited to provide diagnostic biomarkers via liquid biopsy: their miRNA profile can be informative of specific foetal alteration and disease, such as in the case of severe congenital diaphragmatic hernia [ 118 ] or foetal alcohol syndrome [ 63 ]. Likewise, the presence of inflammatory factors in hAF-EVs has been shown to correlate with preterm labour [ 119 , 120 ], while other studies have reported hAF-EVs with procoagulant potential.…”
Section: Evs Derived From Amniotic Fluid: Diagnostics And/or Theranostics?mentioning
confidence: 99%
“…Other studies, however, have shown that increased intrapulmonary release of miRNA-rich, endothelial-derived microvesicles in response to chemical and mechanical lung injuries trigger alveolar macrophage-regulated inflammatory responses and cytokine release ( 96 98 ). Studies of human infants with CDH found that extracellular vesicle concentrations were higher in infants who underwent temporary tracheal occlusion and died postnatally, than in survivors ( 99 ). Interestingly, when the fetal amniotic and tracheal fluid of non-survivors were examined, a different profile was observed before and after the FETO procedure.…”
Section: Extracellular Vesicles and Mirna In Cdhmentioning
confidence: 99%
“…Interestingly, when the fetal amniotic and tracheal fluid of non-survivors were examined, a different profile was observed before and after the FETO procedure. Namely, mir-379-5p and mir-889-3p were both over-expressed in pre-FETO amniotic fluid, but mir-223-3p and mir-503-5p were over-expressed in the tracheal fluid at the time of FETO reversal, suggesting that these markers may indicate either disease progression or amelioration, respectively, depending on their balance in tracheal aspirates or amniotic fluid ( 99 ).…”
Section: Extracellular Vesicles and Mirna In Cdhmentioning
confidence: 99%
See 1 more Smart Citation